The Pageant of Literature: A Second Book of Nonfiction - Baum, Alice C. (New York The Macmillan Company, 1964)
The world that is portrayed in nonfiction writing is not the make-believe world of the short story, novel, or play. It is the world of reality as the authors saw or experienced it or as it impressed them.
Keywords: Literature